Islamic legal thought : a compendium of Muslim jurists - Arabi, Oussama, 1954-; Powers, David Stephan; Spectorsky, Susan A. (Susan Ann) (Studies in Islamic law and society ;, 2013)
In Islamic Legal Thought: A Compendium of Muslim Jurists, twenty-three scholars each contribute a chapter containing the biography of a distinguished Muslim jurist and a translated sample of his work. Jurists of the formative, classical and modern periods are represented.